2014
DOI: 10.1002/eqe.2417
|View full text |Cite
|
Sign up to set email alerts
|

Disorder and damage of base‐isolated medical facilities when subjected to near‐fault and long‐period ground motions

Abstract: SUMMARY A series of full‐scale shaking table tests were conducted at E‐Defense for a four‐story base‐isolated hospital. The operation room in the specimen was chosen for detailed examination of its disorder and damage during large ground motions. It was arranged with various medical appliances in as a realistic manner as possible, and the appliances were characterized by casters installed at the bottom to ensure mobility. Two types of ground motion, the near‐fault ground motion and long‐period ground motion, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 26 publications
0
51
0
2
Order By: Relevance
“…Some such cases included: (i) microwaves moving several metres across rooms, (ii) heating, ventilation, and air-conditioning (HVAC) units sitting on top of roofs of multi-storey buildings being displaced, (iii) books and computers sliding off shelves and tables, and (iv) contents sliding on floors. In addition, recent experimental studies have not only reproduced the observed damage, but have also significantly improved our understanding of contents behaviour during earthquakes and enabled us to develop strategies to mitigate their impact [1][2][3][4][5][6][7][8][9][10]. Although sliding or movement of objects can result in economic loss and injury, mitigating the movement may be uneconomical.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some such cases included: (i) microwaves moving several metres across rooms, (ii) heating, ventilation, and air-conditioning (HVAC) units sitting on top of roofs of multi-storey buildings being displaced, (iii) books and computers sliding off shelves and tables, and (iv) contents sliding on floors. In addition, recent experimental studies have not only reproduced the observed damage, but have also significantly improved our understanding of contents behaviour during earthquakes and enabled us to develop strategies to mitigate their impact [1][2][3][4][5][6][7][8][9][10]. Although sliding or movement of objects can result in economic loss and injury, mitigating the movement may be uneconomical.…”
Section: Introductionmentioning
confidence: 99%
“…The world-largest full-scale 3-dimentional shaking table at E-Defense laboratory in Kobe, Japan was first used to understand the seismic behaviour of non-structural components in high-rise buildings [3] and sliding behaviour of furniture and anchoring force to long-period earthquake motions [2], followed by a series of comprehensive examination of safety and functionality of based-isolated medical facilities [4][5][6]. Similarly, Yeow et al [7] conducted shaking table tests to verify current modelling techniques used in contents sliding simulation, and concluded that the static friction coefficient reasonably estimates the kinetic friction coefficient and the relationship between the force and sliding displacement can be approximated as being elastoplastic.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of different seismic isolation systems on the performance of attached equipment that behaves like viscously damped linear oscillators has been studied at various levels in [6,[14][15][16][17][18][19][20][21]. Furukawa et al [23] studied the effects of vertical motion on the structure and its contents, while Shi et al [24] focused on the seismic performance of the contents. Shake table tests of a full-scale, four-storey, base-isolated reinforced-concrete specimen representing a medical facility housing a wide variety of NCS, including furniture and medical equipment, were carried out by the Nakashima group [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The values were obtained from design documents that presented the results of time history analyses under ground motions adopted in the Japanese design code (Japanese Ministry of Construction). To protect the various contents in the structure, the floor acceleration is generally recommended to 3 m/second 2 or less . The simulation results show that 3 types of isolation have larger accelerations than the recommended value.…”
Section: Multistory Base‐isolated Prototypementioning
confidence: 99%